Le Corps animal comme puissance subversive des normes architecturales. Retour réflexif sur cinq cas d’étude - Léa Mosconi (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The human body — male, and able-bodied — has long served as a model for architects and urban planners, making it a standard and a scale for architectural projects. This article proposes to grasp what the animal body, considered outside of the norm, does to standardized space through the analysis of several cases: a performance including a pony at the Nantes National Higher School of Architecture (ENSA Nantes), the menagerie du Jardin des plantes in Paris, the Paris Zoological Park in Vincennes, an urban farm in Strasbourg and finally, a fictional evolving farm project.